Wood Volume of Eucalyptus Clones Established Under Different Spacings in the Brazilian Cerrado. Issue 4 (18th June 2021) - André, Jéssica L; Oliveira, Rodrigo de S; Sette, Carlos R; Alfenas, Acelino C; Zauza, Edival Ângelo V; de Siqueira, Leandro; Novaes, Evandro
Abstract: Eucalyptus plantations are expanding in Brazil to meet growing demands for wood-based products, such as pulp, paper, and bioenergy. New clones and silvicultural adjustments are needed with the advance of eucalypts to new regions within Brazil. This study's objective was to evaluate the effect of variable spacing on the development of six Eucalyptus clones cultivated in the Cerrado region of Brazil. These clones were evaluated in a systematic design, with 23 spacing treatments and five biological replicates. Spacing per tree ranged from 1.20 m 2 to 21 m 2 . At two, four, and six years after planting, diameter at breast height (DBH) and height of all trees were measured to estimate wood volume. Regression models were fitted for each trait (DBH, height, and wood volume) and showed that DBH growth was positively affected by spacing, especially at four and six years after planting (R 2 > 0.58). Consequently, estimates of individual volume per tree also had a positive relationship with spacing. Total stand volume, on the other hand, was higher under densest spacings. The GG100 clone outperformed all other clones, with higher stand wood volume, especially under the densest spacings. The CCL55 clone is a promising genotype, especially under dense plantations.